PENGARUH DUKUNGAN SOSIAL DAN KEPERCAYAAN DIRI TERHADAP KECEMASAN MENGHADAPI DUNIA KERJA - Wijaya, Dimas Adi; Sari, Laily Lolita; Sandiasih, Komang Mahadewi (Psikosains: Jurnal Penelitian dan Pemikiran Psikologi, 2024)
Background: Students are expected to be able to complete their studies andobtain a bachelor's degree. Then they are also required to prepare to enter theworld of work. Not a few students who are in their final semester beforegraduation feel less confident in their abilities. Likewise, support from family orthe environment certainly influences the job search process. Objective: Thisresearch was conducted to determine the influence between self-confidence andsocial support and anxiety about facing the world of work in final year students.Method: This research uses multiple linear regression analysis methods intesting to determine the magnitude of the influence between anxiety about facingthe world of work and self-confidence and social support. Result: Thecontribution of the variable influence of self-confidence and social support toanxiety in the world of work simultaneously produces a percentage of 42.2%which is proven to be very significant with a P value of 0.0001 with an F valueof 41.910